“Brasinoesteroides como inductor de floración y cuajado de frutos en el cultivo de maracuyá (Passiflora Edulis Var. Flavicarpa) en la zona de Quevedo” - Piedrahita Yun On, Edison Omar (2021)
Passion fruit cultivation is present throughout the Ecuadorian coastline and offers a profitable alternative for small producers who see this activity as a way to obtain income in a perennial way, however, the low technological level that is being used for this crop each time the productive capacity of this fruit is diminishing in the country, which has a high demand in the American and European markets. The present investigation offers an alternative to increase productivity through floral induction using hormonal treatments based on brassinosteroids (BRs) T1 and commercial cytokinins extracted from coconut water T2, within a randomized complete block design where the index of flowering, fruiting index, vegetative growth and fruit weight, in which the T1 treatment reached the highest averages with the exception of vegetative growth where its effectiveness is evidenced in the productive stage of the crop. Keywords: Brasinolides, phytohormones, productivity, passion fruit.